Comparison of Predicted Complexity of Coronary Lesions with Duke Treadmill Score on Various Risk Factors for Coronary Heart Disease - D Rubiyaktho (ACI (Acta Cardiologia Indonesiana), 2017)
Background: According to Framingham Study, independent risk factors for coronary heart.....